LATEST TRENDS IN CONTINGENCY ANALYSIS OF POWER SYSTEM - VinayP.Doshi; Sadanand A. Salgar; Prof.Shravan Kumar Akireddy (International Journal of Innovations in Engineering Research and Technology, 2021)
Contingency plans based on N-1 and N-2 contingencies are already very much usedbyutilities. Artificial intelligent methods are new trends for analysing the contingencyscenarioalong with state of art congestion management. This gives extra backup and boost to reliableoperation under contingent scenario of power system. This paper envisages the summary of allthose efforts.